2008
DOI: 10.1073/pnas.0706658105
|View full text |Cite|
|
Sign up to set email alerts
|

Confinement of caspase-12 proteolytic activity to autoprocessing

Abstract: Caspase-12 is a dominant-negative regulator of caspase-1 (IL-1β-converting enzyme) and an attenuator of cytokine responsiveness to septic infections. This molecular role for caspase-12 appears to be akin to the role of cFLIP in regulating caspase-8 in the extrinsic cell death pathway; however, unlike cFLIP/Usurpin, we demonstrate here that caspase-12 is catalytically competent. To examine these catalytic properties, rat caspase-12 was cloned, and the recombinant enzyme was used to examine the cleavage of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 14 publications
4
36
0
1
Order By: Relevance
“…However, the role of this protease in neuronal demise in the ischemic brain remains to be determined. In fact, it was proposed that caspase-12 acts mainly as a dominant negative in the regulation of caspase-1 activity and the main role of the proteolytic activity of caspase-12 may be in the processing of the protease (Roy et al, 2008).…”
Section: Endoplasmic Reticulum (Er) Stress In Brain Ischemiamentioning
confidence: 99%
“…However, the role of this protease in neuronal demise in the ischemic brain remains to be determined. In fact, it was proposed that caspase-12 acts mainly as a dominant negative in the regulation of caspase-1 activity and the main role of the proteolytic activity of caspase-12 may be in the processing of the protease (Roy et al, 2008).…”
Section: Endoplasmic Reticulum (Er) Stress In Brain Ischemiamentioning
confidence: 99%
“…Of note, although the autocatalytic activity of caspase-12 is sufficient for subunit separation, it does not allow prodomain removal (Roy et al, 2008). Without prodomain removal, caspase-12 is capable only of self-cleavage (Roy et al, 2008), and overexpression of caspase-12 under conditions in which only autoprocessing occurs therefore does not result in apoptosis, likely due to an extremely limited substrate set prior to removal of the prodomain (Nakagawa and Yuan, 2000;Fujita et al, 2002;Kalai et al, 2003;Roy et al, 2008). Removal of the caspase-12 prodomain can be achieved through a number of mechanisms, one of which is cleavage by mcalpain.…”
Section: Pathways Leading To Er Stress-induced Apoptosismentioning
confidence: 99%
“…They trigger inflammation by activating caspase-1, which cleaves pro-IL-1b and pro-IL-18 into their mature active forms. We have previously shown that a second member of the caspase-1 subfamily, caspase-12, which is catalytically inactive in humans and attenuated in rodents (6), acts as an inhibitor of both the inflammasome and NF-kB pathways (7)(8)(9). Expression of human caspase-12 is predominately confined to African descendents and is associated with dampened proinflammatory cytokine production and sepsisrelated mortality (8).…”
mentioning
confidence: 99%